11. SURVEY ON MICROBIOLOGICAL CHARACTERISTICS OF PATIENTS WITH HOSPITAL-ACQUIRED INFECTIONS IN THE INTENSIVE CARE AND ANTI-POISONING DEPARTMENT OF GIONG RIENG MEDICAL CENTER DURING 2018 - 2020 (Vietnam Journal of Community Medicine, 2023)
Objective: Survey microbiological characteristics of patients with hospital-acquired infections in the intensive care and anti-poisoning department of Giong Rieng medical center during 2018 - 2020.Subjects and methods: A retrospective descriptive study on 179 patients with 229 microbiological results in the inpatient medical records of patients treated at the Intensive Care Unit - Poison Control Department of Giong Rieng District Health Center, using antibiotics from January 1st, 2018, to December 30th, 2020.Results: Mainly Gram (-) bacteria causing nosocomial infections in which A. baumannii accounted for the highest rate at 43.2%, K. pneumoniae 10%. Gram (+) bacteria were mainly S. aureus, accounting for 8.1%. In Ventilator associated pneumonia (VAP), the main agent was A. baumannii, accounting for 56.7%. In hospital septicemia B. cepacia was the most common bacteria, accounting for 18.18%. The most common bacteria in urinary tract infection (UTI) was E. faecalis 47.4%, in catheter infection was A. baumannii 46.2%. In intra-abdominal infection, was E. coli 25%.Conclusion: Gram (-) bacteria that caused nosocomial infection were mainly A. baumannii. Gram (+) bacteria were mainly S. aureus. In VAP, the main agent was A. baumannii. Nosocomial septicemia (B. cepacia). UTI was E. faecalis, catheter infection was A. baumannii and intra-abdominal infection was E. coli.
Keywords: Nosocomial infection, Intensive Care Unit.